(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): The study aims to determination the effect of aeromedical evacuation program on flight medics’ practices. Method: A pre-experimental design is carried in army aviation bases in Iraq, for the period of February 1st 2019 to September 25th 2019. Non-probability “purposive” sample of (30) flight medics are selected from army aviation bases. Non-probability “purposive” sample of (30) flight medics are selected from army aviation bases. The questionnaire is composed of two main parts (demographic characteristics of the flight medics, and the second part involves five domains which as (67) items concerning flight medics’ practices regarding first aid of emergency casualties format, the researcher used SPSS version 20 to analyze the data. The reliability of the participant responses was estimated by alpha correlation (r) practice test was (r= 0.94), and content validity of the instrument was determined through a panel of (twenty-five) experts. Data was analyzed through the use of descriptive and inferential statistical analysis. Results: The results of the pretest for flight medics revealed that flight medics’ practices about five domains of aeromedical evacuation program toward emergency casualties was moderate, while the posttest I and II results shows that flight medics’ practices was improved to high level because of the positive impact of the instruction program, and there were significant association between the effectiveness of present program on flight medics’ practices and there level of education at P?0.05. Conclusion: The study concluded that the present program was effective on flight medics’ practices. Recommendation: The study recommended to increase the training courses for flight medics inside and outside Iraq, and included the present program on their plan of training.